Life stage and population density of Plutella xylostella affect the predation behavior of Euborellia annulipes - Nunes, Gilmar da Silva [UNESP]; Dantas, Thais Aparecida Vitoriano; de Souza, Mileny dos Santos; do Nascimento, Izabela Nunes; de Luna Batista, Jacinto; Malaquias, José Bruno (Wiley, 2019)
The diamondback moth (DBM), Plutella xylostella (L.) (Lepidoptera: Plutellidae), is the main pest of brassica crops worldwide. The ringlegged earwig, Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae), has been reported as a potential predator of lepidopteran larvae, including this pest, and may therefore be used for biological control. Knowledge about predator–prey interactions is important to establish pest management strategies. Therefore, the objective of this work was to evaluate the influence of the developmental stage (larva and pupa) and density of P. xylostella on the preference and functional response of E. annulipes adult females. We used choice and no-choice tests to evaluate the foraging behavior and preference of E. annulipes on DBM life stages and varied prey density to assess the type of functional response of the ringlegged earwig. Larvae were preferred over pupae, and the predator’s functional response was type II for both prey stages. Our results report the potential of E. annulipes as a biocontrol agent of P. xylostella. Understanding their interactions may help in decision-making and optimization of integrated management strategies.
Keywords: Anisolabididae; Brassicaceae; Dermaptera; diamondback moth; earwig, IPM; functional response; integrated pest management; Lepidoptera; Plutellidae; predator–prey interactions